Employees’ perception on engagement and its relationship to HRM practices - Yahya, Khulida Kirana (2012)
﻿The paper aims to examine the relationships between human resource management (HRM) practices and employee engagement. HRM practices consist of training and development, financial recognition, non-financial recognition, fringe benefits and supervisory, while employee engagement is a single dimensional construct. A total of 340 questionnaires were distributed to operational level employees, comprising of production operators, trainers, assistant team leaders, and team leaders. A total of 306 questionnaires were returned and used for further analysis. The data were analyzed using Pearson correlation and regression analysis to investigate the relationship between HR practices and employee engagement. The findings exhibited that there were significant and positive relationships between all HRM practices dimensions and employee engagement. The regression analysis result indicated that only fringe benefits and non-financial recognition had influenced employee engagement substantially. Furthermore, the regression results also showed that 30% of total variance of employee engagement was explained by human resource practices dimensions. This denotes that HRM practices play a vital role in promoting employee engagement. Finally, discussions, recommendations as well as conclusion of the study were also highlighted.